2022
DOI: 10.3389/fimmu.2022.837250
|View full text |Cite
|
Sign up to set email alerts
|

Innate Lymphoid Cells in the Central Nervous System

Abstract: Immune cells are present within the central nervous system and play important roles in neurological inflammation and disease. As relatively new described immune cell population, Innate Lymphoid Cells are now increasingly recognized within the central nervous system and associated diseases. Innate Lymphoid Cells are generally regarded as tissue resident and early responders, while conversely within the central nervous system at steady-state their presence is limited. This review describes the current understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 142 publications
0
5
0
Order By: Relevance
“…Second, activated phospholipase in leukocytes promotes secretion of active substances, e.g., prostaglandins, eicosanoids, platelet activating factors, and leukotrienes, which induce vasoconstriction and prolong platelet aggregation [ 29 ]. At last, some immune modulators and proinflammatory cytokines are secreted by infiltrated leukocytes in the penumbra zone around the infarct center, which may damage more neurons [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, activated phospholipase in leukocytes promotes secretion of active substances, e.g., prostaglandins, eicosanoids, platelet activating factors, and leukotrienes, which induce vasoconstriction and prolong platelet aggregation [ 29 ]. At last, some immune modulators and proinflammatory cytokines are secreted by infiltrated leukocytes in the penumbra zone around the infarct center, which may damage more neurons [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being the most important component of innate immunity, NK cells are key players in adaptive immunity (Caligiuri, 2008). Over the past decade, accumulating evidence has revealed that CNSinfiltrating NK cells modulate neuroinflammation, establishing an important role for NK cells in neurodegenerative diseases (Poli et al, 2013;Menees and Lee, 2022;Wang and van de Pavert, 2022). In patients with ALS, NK cells are elevated in the peripheral blood (Gustafson et al, 2017;Murdock et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes, eosinophils, and neutrophils are part of the innate immune system. 12 , 13 The adaptive immune system is essential in recognizing the antigen of tumors and providing helper and killer functions for tumors but often fails to establish immune memory. 14 , 15 In addition, activated dendritic cells (DCs) can present antigens to CD4 + T cells and recruit monocytes or macrophages to the tumor site.…”
Section: Discussionmentioning
confidence: 99%